The Influence of Generation Z Peer Circles on The Development of English-Speaking Skills - Nafha Sepani (CV Grasta Glory, 2025)
This research looks at how friendship groups (peer circles) affect the English-speaking skills of sixth-semester students in the English Education Program at PGRI Silampari University. Generation Z students, who often use social media like TikTok and WhatsApp, are used to talking and sharing through digital platforms. The study used a simple survey of 21 students to determine how often and how well they speak English with their friends. The results show that many students feel more comfortable speaking English with their close friends. Friends also help motivate and provide feedback to improve speaking skills. Some students reported confidence in their pronunciation and vocabulary, but many still feel unsure when speaking in public. This shows peer circles are helpful, but students still need more practice. Teachers can support students by giving more group speaking activities and using peer support to help them feel more confident and improve their English skills.